Teacher Questioning Strategies Employed in Speaking Classes in EFL Setting: A Study of Classroom Interaction - Risna Saswati (Scope : Journal of English Language Teaching, 2022)
This study investigates the employment of teachers questioning strategies in Speaking classes in an EFL setting. This study intends to find out how the teachers employ those questioning strategies as well as to investigate whether the type of questioning strategies and the way teachers apply those types of questioning strategies assist learners in engaging in classroom interaction. The participants were teachers teaching Speaking classes and learners attending the classes. This study employed descriptive qualitative research using videotaped class observations and transcription as the techniques of data collection. The teachers’ questioning strategies and learners’ responses are highlighted and analyzed. The referential and follow-up questions were applied in the while-speaking stage to gain information from the learners and the class. The questions were addressed to the class and individuals to assist learners getting involved in the interaction. The display and follow-up questions were addressed more in a post-speaking stage, used for an assessment for today’s lesson. The results reveal that teachers mostly use display questions in the pre-speaking stage to introduce the new lesson, set the class mood, as the motivating strategies, and attract the class’s attention to the new lesson. The type of questions employed by the teachers are effective to make the learners involved in classroom interaction must be based on the needs and time. The way teachers address questions should be started in the class, in small groups, and with individuals. Teacher wait-time is one of the facilities for teachers are expected to provide learners as a learning opportunity.